A validation of dynamic hygrothermal model with coupled heat and moisture transfer in porous building materials and envelopes. (November 2020) - Dong, Wenqiang; Chen, Youming; Bao, Yang; Fang, Aimin
Abstract: For predicting and evaluating the hygrothermal performance of buildings, predicting the risk of mould growth and improving the durability of the structure, an accurate dynamic hygrothermal model for coupled heat and moisture transfer in porous building materials and envelopes is necessary. The dynamic hygrothermal models need to be fully validated. However, literature review revealed that these models have not been fully validated. This study fully validates the Künzel model and the Liu model which are popular but not comprehensively validated. The results of both the models simulated by Fortran code and COMSOL Multiphysics are compared with analytical solutions, other model simulated solutions, and the data from two published experimental datasets. The simulated results of both models are in good agreement with the results in the existing published literature. All errors between the simulated and experimental results are within acceptable levels within the hygroscopic range. Near over-hygroscopic region (relative humidity is less than but close to 95%), the Liu model is more accurate than the Künzel model. The investigations in this study demonstrate that the two models are accurate and applicable for hygrothermal simulations within the hygroscopic range, the Künzel model is not applicable near over-hygroscopic region. It also boosts confidence for the application of two dynamic models for coupled heat and moisture transfer in building hygrothermal simulations. Highlights: Literature review reveals that validation for hygrothermal models are not sufficient. Two popular dynamic hygrothermal models are fully validated. Both models have acceptable simulation accuracy within hygroscopic region. Liu model is more accurate than Künzel model near over-hygroscopic region.